FENOMENOLOGI SIMBOLIK AL-QUR’AN: KRITIK EPISTEMOLOGI ATAS BUKU PENGANTAR FENOMENOLOGI AL-QUR’AN DIMENSI KEILMUAN DI BALIK MUSHAF UTSMANI - Nunung Lasmana (Institut Agama Islam Negeri (IAIN) Keiri, 2017)
In the midst of a general phenomenon of rampant tafsir study that occurred in the middle of Muslims, the study of the interpretation of the Mushaf or symbolic aspects of the format of the Qur’an is still very minimal. This effort was done by Lukman Abdul Qohar Sumabrata, Lukman Saksono, and Anharudin. The method of interpretation, they describe in their work entitled Introduction to Phenomenology of the Qur’an Scientific Dimension behind the Ottoman Manuscripts. The method seeks to interpret the Qur’an from a different point of view, namely to interpret the Qur’an through its format and structure. This interpretation leads to the variables of the Qur’an, in which each variable has a meaning and is interconnected with one another. This is because there is a significant difference between the interpretation of symbolic phenomenology and other interpretations that lie in the object of interpretation. The object of the method of interpretation of symbolic phenomenology is not the verbal language, but the symbol and structure of the Qur’an that is contained in the Ottoman Manuscripts. Therefore, this method cannot be categorized as an interpretation of the Qur’an. The interpretation of symbolic phenomenology here is not an interpretation of the content of verses of the Qur’an as it is known in general. However, this interpretation is done to find the scientific messages behind the symbolic elements in the Qur’an, such as letters, numbers, surahs, juz, and ‘ain signs. So, the problem in this method is about whether the Qur’an consists only of the composition of the 6236 number of verses? Why is the Qur’an arranged in sections called juz, and why are there 30? Is the ‘ain’ sign only a stop sign? Why is the letter ‘ain not another letter used? and so forth.